Care-seeking patterns and timely access to care among survivors of sexual violence in North Kivu, the Democratic Republic of the Congo: a retrospective file-based study - Hanna Reinholdz; Anette Agardh; Meggy Verputten; Joseph Byenda; Helena Frielingsdorf (Global Health Action)
Background Sexual violence is widespread in war-torn North Kivu province in the Democratic Republic of the Congo (DRC). Timely access to care is crucial for the healing and wellbeing of survivors of sexual violence, but is problematic due to a variety of barriers. Through a better understanding of care-seeking behaviours and factors influencing timely access to care, programmes can be adapted to overcome some of the barriers faced by survivors of sexual violence. Objective The aim of this study was to describe demographics, care-seeking patterns and factors influencing timely care-seeking by survivors of sexual violence. Methods Retrospective file-based data analysis of sexual violence survivors accessing care within two Médecins Sans Frontières (MSF) programmes supporting the Ministry of Health, in North Kivu, DRC, 2014–2018. Results Most survivors (66%) sought care at specialised sexual violence clinics and a majority of the survivors were self-referred (51%). Most survivors seeking care (70%) did so within 3 days. Male survivors accessing care were significantly more likely to seek care within 3 days compared to females. All age groups under 50 years old were more likely to seek care within 3 days compared to those aged 50 years and older. Being referred by the community, a family member, mobile clinic or authorities was significantly associated with less probability of seeking care within 3 days compared to being self-referred. Conclusion Access to timely health care for survivors of sexual violence in North Kivu, DRC, is challenging and varies between different groups of survivors. Providers responding to survivors of sexual violence need to adapt models of care and awareness raising strategies to ensure that programmes are developed to enable timely access to care for all survivors. More research is needed to further understand the barriers and enablers to access timely care for different groups of survivors.